2002
DOI: 10.1046/j.1442-200x.2002.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and diastolic function in children with chronic renal failure

Abstract: The technique of CAPD has some advantages as a renal replacement therapy for preserving cardiac functions as compared with hemodialysis. However, it must be remembered that patients with hemodialysis have features that effects cardiac status, such as higher volume load and higher afterload (hypertension).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…[26][27][28][29] However, others could not confirm these findings and indicated that abnormalities in diastolic filling may occur early and before LVH and systolic dysfunction. [4,7] We did not find a significant correlation between LVMI and the E/A ratio, which was consistent with some reports in literature. [4,7,30] Because of the absence of a relation between LVMI and the E/A ratio, the diastolic dysfunction in our patients could not be fully attributed to an increased LVMI.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[26][27][28][29] However, others could not confirm these findings and indicated that abnormalities in diastolic filling may occur early and before LVH and systolic dysfunction. [4,7] We did not find a significant correlation between LVMI and the E/A ratio, which was consistent with some reports in literature. [4,7,30] Because of the absence of a relation between LVMI and the E/A ratio, the diastolic dysfunction in our patients could not be fully attributed to an increased LVMI.…”
Section: Discussionsupporting
confidence: 92%
“…[4,[7][8][9] In adult patients on CAPD, LVH initially is of similar degree as in HD patients, but worsens with longer duration of treatment associated with systolic function and poor BP control. [10,11] In contrast to these findings, Atalay et al [4] demonstrated that IVST, PWT, and LVMI were significantly increased and LV volume/mass ratio was decreased in children on HD compared to those on CAPD, CRI, and control groups. [10,11] In the present study, statistically significant increases in IVST, PWT, and LVMI were observed in both HD and CAPD dialysis groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations